Pengaruh size dan beta terhadap return pada perusahaan kecil dan besar yang terdaftar di Bursa Efek Indonesia periode 2010-2014 - Y.S. Soefian Nur Hidayat; Sri Hasnawati; Ernie Hendrawaty (STIE Perbanas Surabaya, 2019)
This study aims to empirically prove the effect of size and beta on returns. The analytical method used in this research is descriptive and statistical analysis methods. This research was conducted in the period 2010-2014 with a sample of 953 public companies. The results of the study stated that the effect of size on stock returns in small companies is stronger than large companies. The effect of beta on stock returns is higher in small companies than in large companies. Based on these findings, large companies must be able to improve their performance so that they are able to increase stock returns so investors are interested in investing.